Efforts to Increase Motivation and Completeness in Learning Mathematics Through the Wordwall-Assisted Problem Based Learning Model - Cyrenia Novella Krisnamurti (Edumaspul: Jurnal Pendidikan, 2024)
There are several factors that influence student learning completeness, one of which is learning motivation, an internal factor that students must possess. This research aims to improve the motivation and learning completeness in mathematics through the Problem-Based Learning (PBL) model assisted by Wordwall in Exponential and Logarithmic materials for the 10th-grade students at SMA Santa Maria Yogyakarta in the 2023/2024 academic year. This study is a Collaborative Classroom Action Research. The subjects of this research are all 10th-grade students at SMA Santa Maria Yogyakarta. The research procedures were carried out in two cycles, each consisting of four stages: 1) planning, 2) implementation, 3) observation, and 4) reflection. The variables in this study are the Problem-Based Learning (PBL) model assisted by Wordwall, learning motivation, and student mathematics learning completeness. Data collection techniques in this study included observation, questionnaires, and tests. The research instruments used were observation sheets, questionnaire sheets, and test sheets. The percentage of student motivation in cycle I showed that 0% had very high motivation, 25.71% high, 40% moderate, 34.29% low, and 0% very low. However, student motivation in cycle II increased, with 2.86% in the very high category, 65.71% in the high category, 17.14% in the moderate category, 14.29% in the low category, and 0% in the very low category. Based on these results, it can be seen that there was an increase in student motivation from low to moderate, from moderate to high, and from high to very high. The mathematics learning process using the Problem-Based Learning model assisted by Wordwall showed an increase in student test results. In cycle I, the average score reached 94.29, with 19 out of 23 students meeting the minimum completeness criteria (KKM), while in cycle II, the average score reached 95.68, with 21 out of 23 students achieving the KKM. It can be concluded that the Problem-Based Learning model assisted by Wordwall can improve the motivation and learning completeness in mathematics of 10th-grade students at SMA Santa Maria Yogyakarta